Development of an Efficient Strategy to Improve Extracellular Polysaccharide Production of Ganoderma lucidum Using L-Phenylalanine as an Enhancer - Ma, Zhongbao; Xu, Mengmeng; Wang, Qiong; Wang, Feng; Zheng, Huihua; Gu, Zhenghua; Li, Youran; Shi, Guiyang; Ding, Zhongyang (Frontiers in Microbiology, 2019)
Ganoderma lucidum is a species of basidiomycetes well known for edible and medicinal properties. Based on the simulation results of model iZBM1060 in our previous research, the effect of L-phenylalanine on G. lucidum extracellular polysaccharide (EPS) was investigated in this study. EPS production reached 0.91 g/L by adding 0.4 g/L L-phenylalanine after 24 h culture, which increased by 62.50% to control. Transcriptome and genome analysis showed that L-phenylalanine deaminase and benzoate 4-hydroxylase related to L-phenylalanine metabolism were significantly up-regulated, while the cell wall mannoprotein gene was down-regulated. It was observed via transmission electronic microscopy that the thickness of cell wall decreased by 58.58% in the case of L-phenylalanine. These results indicated that L-phenylalanine promoted the EPS production by decreasing cell wall thickness, which resulted in the increased cell wall porosity. This study provided an efficient strategy for fungal polysaccharides production with high output and low cost.